The Task-Based Evaluation of the English for Nusantara Textbook to Curriculum Merdeka Principles - Idris, Bayu Romli; Muamaroh, M; Ratih, Koesoema (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the tasks in English for Nusantara (Kementerian Pendidikan, 2022) based on the theme "Exploring Fauna of Indonesia," whether they are congruent with Task-Based Language Teaching (TBLT) principles and the Merdeka Curriculum. From the list of tasks, 25 were chosen and content analysed. Tasks are categorized based on type, phases, authenticity and alignment with values of the Merdeka Curriculum such as student agency, collaborative skills, HOTS- Higher Order Thinking Skills, and Pancasila value. Qualitative content analysis was used to structure the data according to categories and themes, using systematic coding and NVivo software. The study seeks to identify strengths and weaknesses in promoting critical thinking and student-centred learning. The results indicate that information-gap tasks (44%) were the most common task type, and reasoning-gap tasks (32%) and opinion-gap tasks (24%) followed. The task cycle was the most commonly focused phase (52%), less attention was paid to the pre-task (28%) and post-task (20%) phases. Task authenticity showed that 48% were highly authentic. The alignment of Merdeka Curriculum, focused on student agency (44%) and collaboration (32%), was lower for HOTS (20%) and Pancasila values (4%). The research recommends refinement of the integration of HOTS and worth Pancasila to realize a more complete curriculum goal.